Caracterização patológica e molecular do vírus da Bouba Aviária como contribuição para elaboração de padrão de condenação para carcaças de perus - Ferreira, Bruna Custódio (2015)
This study described the first outbreak of avian fowlpox in Brazil in previously vaccinated turkeys and also established, in an attempt to help the Federal Inspection Service, a standard of condemnation for carcasses with lesions characteristic of fowlpox. The turkeys had crusted macroscopic lesions on their skin, suggestive of avian fowlpox in the head and neck and no additional clinical signs were observed. The mortality rates in the flock did not change. In the slaughterhouse, 30 carcasses were removed from the slaughter line to collect damaged skin fragments for its characterization and research of the virus. The samples were fixed in formalin, embedded in paraffin, cut into sections of 6 microns and stained with hematoxylin-eosin for viewing in microscope. The agent identification was performed by conventional PCR with subsequent sequencing of the gene fpv167. On histopathology were observed: hyperkeratosis, acanthosis and hydropic degeneration; the presence of eosinophilic intracytoplasmic inclusion corpuscles (Bollinger) was observed in keratinocytes in 46.6% of samples. The PCR reaction was positive in 83.3% of samples. Using both diagnostic techniques was determined that 93.3% of the samples were positive for fowlpox. In the phylogenetic study, the samples show 100% of identity to each other suggesting that the outbreak occurred by a single virus strain. The sequenced gene fragment did not allow differentiation between strains of virus that infect turkeys, chickens or vaccinal strain. The fowlpox virus is avian species specific, and there are no reports of its occurrence in mammals. According to the macroscopic and microscopic characteristics of the skin lesions is not justified total condemnation of turkey\'s carcasses affected by avian fowlpox, except in cases of cachexia, disgusting aspect and other specifications at Federal Inspection Service regulations. Studies including the sequencing of other genes are needed to better viral characterization and can assist in identifying origin of the etiologic agent responsible for the outbreak and its possible sources.